Partners in crime: The feedback loop between metabolic reprogramming and immune checkpoints in the tumor microenvironment - Benito-Lopez, Jesus J.; Marroquin-Muciño, Mario; Perez-Medina, Mario; Chavez-Dominguez, Rodolfo; Aguilar-Cazares, Dolores; Galicia-Velasco, Miriam; Lopez-Gonzalez, Jose S. (Frontiers in Oncology, 2023)
The tumor microenvironment (TME) is a complex and constantly changing cellular system composed of heterogeneous populations of tumor cells and non-transformed stromal cells, such as stem cells, fibroblasts, endothelial cells, pericytes, adipocytes, and innate and adaptive immune cells. Tumor, stromal, and immune cells consume available nutrients to sustain their proliferation and effector functions and, as a result of their metabolism, produce a wide array of by-products that gradually alter the composition of the milieu. The resulting depletion of essential nutrients and enrichment of by-products work together with other features of the hostile TME to inhibit the antitumor functions of immune cells and skew their phenotype to promote tumor progression. This review briefly describes the participation of the innate and adaptive immune cells in recognizing and eliminating tumor cells and how the gradual metabolic changes in the TME alter their antitumor functions. In addition, we discuss the overexpression of the immune checkpoints and their ligands as a result of nutrient deprivation and by-products accumulation, as well as the amplification of the metabolic alterations induced by the immune checkpoints, which creates an immunosuppressive feedback loop in the TME. Finally, the combination of metabolic and immune checkpoint inhibitors as a potential strategy to treat cancer and enhance the outcome of patients is highlighted.